Determination of primary electron beam parameters in a Siemens Primus Linac using Monte Carlo simulation - Seifi Makrani, Danial; Hasanzadeh, Hadi; Allahverdi Pourfallah, Tayyeb; Ghasemi, Arash; Jadidi, Majid; Babapour, Hamed (Archives of Advances in Biosciences, 2015)
The Monte Carlo method can be used to describe any technique that approximates solutions to quantitative problems through statistical sampling. This method is considered to be the most accurate method for dose calculation in radiotherapy. For complete modeling of a linear accelerator, it is required that the manufactured information covers all data, but some data such as primary electron energy must be indicated. The purpose of this study was to determine the best primary electron energy for 15 MV photon beam with varying the energy and FWHM. A Monte Carlo model for photon-beam output of a Siemens primus linear accelerator was validated by plotting the energy spectrum of photon beam and calculating the percentage depth dose (PDD) and beam profiles for 10×10 cm2 field. Square 10×10 cm2 field was validated by measurements in water by a farmer chamber. Linac head simulation was performed with BEAMnrc and dose calculation and 3D dose file were produced by DOSXYZnrc. The results were analyzed using MATLAB. It was found a good agreement between calculated PDD and beam profile for 15 MV photon beam using Monte Carlo simulation with primary electron energy of 11 MV and FWHM of 0.4 with maximum dose difference of 1.2% in PDD curves. In conclusion, using primary electron energy of 11 MV and FWHM of 0.4 has very good accuracy in calculating of dose distribution for 15 MV photon beam and it can be considered as a promising method for patient dose calculations.